Management of Pesantren Governance in Improving the Quality of Islamic Education (Multi-site Study at Pondok Pesantren Wali Songo Ngabar Ponorogo and Pesantren Putri Al-Mawaddah Coper Ponorogo) - Yusril Musyafa’, A’ang; Akhyak, Akhyak; Aziz, Abd. (Publisher Cv. Inara, 2025)
This research examines the challenges faced by Islamic boarding schools in educating students, both from internal and external perspectives. The focus of the research is on the planning, organizing, implementation, and supervision of the governance of pesantren at Pondok Pesantren Wali Songo Ngabar Ponorogo and Pesantren Putri Al-Mawaddah to improve the quality of Islamic education. The method used is qualitative with data collection techniques through in-depth interviews, observation, and documentation, as well as single-site and cross-site analysis. The research findings include the importance of transparency, accountability, responsibility, independence, and fairness in every aspect of pesantren governance to create a quality education system. Transparency is evident in financial management and open decision-making. Accountability is realized through adherence to policies and performance evaluations. Responsibility is demonstrated through accountability to the community and regulations. Independence is reflected in the diversification of funding sources and independent program initiatives. Fairness is evident in equal access to education and consistent program evaluation. This research emphasizes that a good governance system is crucial for improving the quality of Islamic education in pesantren.